Judiciário e inclusão: a aplicação do conceito constitucional de pessoas com deficiência na jurisprudência das cortes federais - Magajewski, Fábio Luparelli (2021)
The research aims to analyze the assimilation of the constitutional concept of people with disabilities in decisions taken by the Brazilian federal courts. Initially, it discusses the process of origin and positivization of fundamental rights and the juridical contents of the principles of human dignity and equality, as constitutional and democratic foundations for the persuit for social inclusion. It exposes the historical evolution of disability models, related to the protection granted to them by Brazilian constitutions, highlighting the most recent achievements from the Convention on the Rights of Persons with Disabilities, which instituted the new concept of people with disabilities, incorporating to the Constitution the social model of disability and the inclusion paradigm. The constitutional concept of person with disability is then approached, associating it with the principles of human dignity and equality. Based on this, judicial decisions that apply the concept of person with disability in concrete cases are analyzed, in matters of competence of the common federal justice, found in the jurisprudence of the Supreme Court, the Superior Court of Justice and the five regional federal courts. At the end, some parameters for the judicial application of the concept of people with disabilities are proposed, aiming at an improvement in its jurisprudential approach, in harmony with the Constitution and its inclusive purpose